Efektivitas Pelatihan Online Skrining Depresi Pada Lansia Dalam Meningkatkan Pengetahuan Dan Kepercayaan Diri Tenagan Kesehatan - Warih Andan Puspitosari; Ryan Nuari Pratma (Institut Citra Internasional, 2021)
Background: Mental health is a condition in which a person can develop physically, mentally, spiritually and socially. A disease that often disturbs a person's mental health, especially someone who has entered old age is depression. Screening has the advantage of being simple, easy and relatively inexpensive to use it aims to detect a disease early in a person so that a complete diagnosis can be made and can be given early treatment. Objective: To identify the effect of depression screening training in the elderly on the level of knowledge and confidence of health workers in performing depression screening measures in the elderly. Methods: The research design was quasy experimental with one group pretest and posttest design. The sampling technique used total sampling. The number of samples is 22 people. The intervention was carried out by experts by providing training materials for depression screening in the elderly. Knowledge and confidence were assessed before and after the intervention using a validated questionnaire. Bivariate analysis using Paired sample t-test. Results: There is a significant difference in the level of knowledge of the respondents between the pretest and posttest with a p-value of 0.000 (<0.05). There is a significant difference in the level of self-confidence of the respondents between the pretest and posttest with a p-value of 0.000 (<0.05). Conclusion: There is a significant effect on the level of knowledge and self-confidence of respondents after being given depression screening training in the elderly.